Detection of Biofilm Producing Vibrio parahaemolyticus from Anchovy Fish (Stolephorus indicus) Sold in Puducherry - Vijayan, C.; Ajaykumar, V.; Bhattacharya, A.; Rabins , S. Leonal (Journal of Meat Science, 2017)
Food borne illnesses have major social and economic impacts. The WHO estimates that worldwide food borne and waterborne diarrheal diseases together kill about 2.2 million people annually and in India around 6 per cent of the population. Vibrio parahaemolyticus has recently been recognized as one of the most important food borne pathogens as the leading causal agent of human acute gastro enteritis and also it has the biofilm forming capacity. This study was conducted to detect the biofilms producing Vibrio parahaemolyticus from Anchovy fish (Stolephorus indicus) sold in Puducherry and was isolated as per the standard procedure. A total of 50 samples were screened for presence of Vibrio parahaemolyticus. Out of 50 samples, only 20 samples (40 %) were positive for Vibrio parahaemolyticus. This isolates were further screened for detection of biofilm production ability by using Modified Congo Red Agar (CRA). Out of 20 isolates, only 15 isolates (75%) of Vibrio parahaemolyticus were having biofilm producing ability. This can be a major concern as microorganisms growing in a biofilm can be associated with chronic and recurrent human infections. Such organisms are highly resistant to cleaning, antimicrobial agents and reduce the efficiency of chemicals on sanitization of food processing equipments in food industry.
Keywords: Anchovy fish; Biofilm; Vibrio parahaemolyticus; Foodborne illness